Illicit drugs or medicines taken by parachuting. (23rd December 2015) - Daveluy, Amélie; Géniaux, Hélène; Eiden, Céline; Boucher, Alexandra; Chenaf, Chouki; Deheul, Sylvie; Spadari, Michel; Gérardin, Marie; Miremont‐Salamé, Ghada; Haramburu, Françoise
Abstract: Parachuting (also called bombing) is a method of drug delivery where illicit drugs or medicines are ingested after wrapping the substance. There are little data describing parachuting in the literature. To provide a description of this practice, all cases of parachuting reported to the national addictovigilance network up to 31 December 2014 were identified from spontaneous reports and specific surveillance programs. Cases were described according to the type of substance used, patient age and gender, type of complications, context of use and year of the event. Forty‐five cases of parachute use were identified and most ( n = 43) occurred after 2011. Patients were mostly men (60%), and mean age was 28.9 years. The context of use, known in 19 cases, was mostly recreational. Complications were present in 24 cases, of which eight were serious. The substance was supposed to be 3, 4‐methylenedioxymethamphetamine (MDMA) in the majority of cases (64.4%); research chemicals were more involved in the most recent years. The physical form was mainly granular (51.6%). The wrappers were a cigarette paper (nine cases) and in one case plastic package; in the other cases, the term of parachute was used without further details. The reason for use was not explained in the majority of cases; two patients indicated using a parachute for faster effect than with a methadone capsule. Clinicians should be aware of this delivery form as the results suggest that it is common and can involve a great variability of drugs.